PENGARUH PELATIHAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN - Friska Susanti Butar Butar; Irsutami Irsutami (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2018)
The purpose of this study is to determine the effect of training and work motivation on employee performance. Training measured by the dimensions of skills and knowledge, while working motivation dimension is measured by motives, expectations, and incentives, and the employee's performance can be measured by indicators of quantity of work, quality of work, cooperation, understanding of the task, initiative, discipline and reliability. Respondents in this study were 200 employees of accounting staf who work in manufacturing companies in Batam, technique which is used to analyze this study is simple linear regression analysis. Results of the study found that training and motivation work have positive influence on employee performance. Based on these results it’s advisable for the company to provide adequate training and increase employee motivation to improve the productivity of the company. This study is confined to the accounting staf employees in manufacturing companies in Batam, so further research is recommended to use the different samples and from other types of companies.